The progress principle : using small wins to ignite joy, engagement, and creativity at work - Amabile, Teresa. (Harvard Business Review Press, 2011)
Explains how to foster progress, shows how to remove obstacles, including meaningless tasks and toxic relationships that disrupt employees' work lives, and offers advice on enhancing employees' inner work life.